Gene Size Matters: An Analysis of Gene Length in the Human Genome - Lopes, Inês; Altab, Gulam; Raina, Priyanka; de Magalhães, João Pedro (Frontiers in Genetics, 2021)
While it is expected for gene length to be associated with factors such as intron number and evolutionary conservation, we are yet to understand the connections between gene length and function in the human genome. In this study, we show that, as expected, there is a strong positive correlation between gene length, transcript length and protein size as well as a correlation with number of SNPs and introns. Amongst tissue-specific genes, we find that the longest transcripts tend to be expressed in blood vessels, nerves, thyroid, cervix uteri and the brain, while the smallest transcripts tend to be expressed in the pancreas, skin, stomach, vagina and testis. We report, as shown previously, that natural selection suppresses changes for genes with longer transcripts and promotes changes for genes with smaller transcripts. We also observe that genes with longer transcripts tend to have a higher number of co-expressed genes and protein-protein interactions, as well as more associated publications. In the functional analysis, we show that bigger transcripts are often associated with neuronal development, while smaller transcripts tend to play roles in skin development and in the immune system. Furthermore, pathways related to cancer, neurons and heart diseases tend to have genes with longer transcripts, with smaller transcripts being present in pathways related to immune responses and neurodegenerative diseases. Based on our results, we hypothesise that longer genes tend to be associated with functions that are important in the early development stages, while smaller genes tend to play a role in functions that are important throughout the whole life, like the immune system which requires fast responses.